KERAGAMAN GENETIK, HERTTABILITAS DAN KOEFEIEN VARIASI GENETIK BEBERAPA KARAKTER GALUR MUTAN KEDELAI (Glycine max (L.) MOT.) - Ishak Ishak; Soertini Gandanegara (BERITA BIOLOGI, 1998)
Analysis of genetic variance, heritability and coefficient of genetic variance were carried out for seven characters of soybean mutant lines in M3 generation, which were conducted at CAIR-Field Station, Pasar Jumat, Jakarta.Results showed that the highest of heritability value about 85.50% was obtained for seed weight, and followed by number of pods,biomass of stem and shelpedpods, root/stem ratio, seed weight/ Zpods ratio, and the lowest heritability value was biomass of root around 26,83% Analysis of coefficient of genetic variance from seven characters of soybean mutants indicated value ranging from 10.00-39,50%.From the result of experiment can be concluded that gamma irradiation produced high genetic variability in M3 generation and contributed positively for crops improvement through breeding programme